FREE RADICAL SCAVENGING ACTIVITY OF LEAVES OF BOERHAVIA DIFFUSA - C.C.S.VASUNDHARA; S.GAYATHRI DEVI (International Journal of Pharma and Bio Sciences, 2015)
The oxidative degenerative disorders are caused due to the free radical accumulation in the body and there is a need for new antioxidants from plant sources to protect ourselves from the radicals. The present study was aimed at evaluating the free radical scavenging activity generated by the different extracts (petroleum ether, chloroform, ethanol and aqueous) of leaves of Boerhavia diffusa. The in vitro methods like DPPH, ABTS, nitric oxide, hydroxyl, hydrogen peroxide and superoxide radical scavenging activity were adopted for the study. The scavenging effect of the plant extracts and the standard ascorbic acid showed a dose dependent increase with increase in concentration in percent inhibition (20 – 100 µg/ml). The ethanolic extact of the leaves was found to possess a better scavenging activity at 100µg/ml concentration towards DPPH (60.8±0.21%), ABTS (71±0.31%), nitric oxide (80.4±0.1%), hydroxyl (76.4±0.21%), hydrogen peroxide (74.5±0.17%) and superoxide (79.6±0.26%) radicals. Hence the result of the present study confirms the antioxidant potential of the leaves of Boerhavia diffusa.